PENGARUH PIUTANG TAK TERTAGIH DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS DAN LAPORAN ARUS KAS OPERASI PADA BISNIS PERHOTELAN (STUDI PADA HOTEL BERBINTANG YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Firly Sukma Andini, - (2021)
This study aims to determine the effect of bad debts and receivables turnover on the profitability of a company and the cash flow statements presented by the company. This research focuses on the hotel sector business which is currently increasingly in demand by business people and investors. The method used in this research is the casual- comparative method and the descriptive method. The sampling method in this study used a purposive sampling method by determining several criteria in order to obtain as many as 10 selected companies from 30 listed companies. The data used is secondary data obtained from the company's annual financial statements published on the Indonesia Stock Exchange during 2015 to 2020. The data analysis technique in this study uses multiple linear regression analysis techniques with hypothesis testing using t-test with the help of statistical tests using E software. -Views. This study produces hypotheses in the form of (1) bad debts has no positive or significant effect on profitability, (2) accounts receivable turnover has a positive and significant effect on profitability, (3) bad debts do not have a positive effect on operating cash flow statements, ( 4) receivables turnover has a positive and significant effect on operating cash flow statements, and bad debts and accounts receivable turnover simultaneously have an effect on profitability and operating cash flow statements. Which means that the company's profit and the company's operating cash flow are not affected by the value of bad debts of a company in the hospitality sector, but on the other hand the company's profit and the company's operating cash flow are strongly influenced by the value of a company's receivables turnover. Companies need to have special internal controls to regulate the rate of receivables turnover so that they can help companies survive in competition and develop with the aim of expanding the hotel business itself. This research is expected to help companies and academic activists in adding knowledge about receivables arising from policies made by the company's managerial itself.